2020
DOI: 10.1155/2020/6454281
|View full text |Cite
|
Sign up to set email alerts
|

RiPerC Attenuates Cerebral Ischemia Injury through Regulation of miR-98/PIK3IP1/PI3K/AKT Signaling Pathway

Abstract: Background. Cerebral ischemic stroke is a refractory disease which seriously endangers human health. Remote ischemic perconditioning (RiPerC) by which the sublethal ischemic stimulus is administered during the ischemic event is beneficial after an acute stroke. However, the regulatory mechanism of RiPerC that relieves cerebral ischemic injury is still not completely clear. Methods. In the present study, we investigated the regulatory mechanism of RiPerC in a rat model of ischemia induced by the middle cerebral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Recently, Wei et al have reported that Foxp1 regulates Phosphoinositide-3-Kinase Interacting Protein 1 (Pik3ip1) expression in CD8 + T cells cultures with IL-7. Pik3ip1 is a negative regulator of phosphatidylinositol 3-kinase (PI3K) [ 13 ] and has shown an extensive range of functions such as cardiac hypertrophy, apoptosis, and immune-inflammatory responses [ 14–16 ]. Studies have demonstrated that PI3K/Akt/endothelial nitric oxide synthase (eNOS) signaling pathway activation implicated protective effects of various agents against IRI.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wei et al have reported that Foxp1 regulates Phosphoinositide-3-Kinase Interacting Protein 1 (Pik3ip1) expression in CD8 + T cells cultures with IL-7. Pik3ip1 is a negative regulator of phosphatidylinositol 3-kinase (PI3K) [ 13 ] and has shown an extensive range of functions such as cardiac hypertrophy, apoptosis, and immune-inflammatory responses [ 14–16 ]. Studies have demonstrated that PI3K/Akt/endothelial nitric oxide synthase (eNOS) signaling pathway activation implicated protective effects of various agents against IRI.…”
Section: Introductionmentioning
confidence: 99%
“…The protective effect of PI3K/Akt/eNOS on endothelial cells has been established in numerous studies (25,26). Previous evidence has indicated that miR-98-5p affects apoptosis, inflammation and oxidative stress by regulating the PI3K/Akt signaling pathway (27)(28)(29). Moreover, studies have shown that IGF1R can affect the development of diabetes through the PI3K/Akt/eNOS axis (30)(31)(32).…”
Section: Protective Effects Of Endothelial Progenitor Cell Microvesic...mentioning
confidence: 98%
“…However, reperfusion processes after ischemic attack may further exacerbate brain damage, which is named cerebral ischemia/reperfusion (I/R) injury [5,6]. It is increasingly understood that multiple pathophysiological processes, includ-ing oxidative stress, the inflammatory response, neuronal death, and apoptosis, play a pivotal role in the development of cerebral I/R injury [7][8][9][10]. Thus, treatments based on the above mechanisms are proposed as a promising strategy to attenuate the outcomes of stroke and cerebral I/R injury.…”
Section: Introductionmentioning
confidence: 99%